Chasing behaviour and optomotor following in free-flying male blowflies: flight performance and interactions of the underlying control systems - Trischler, Christine; Kern, Roland; Egelhaaf, Martin (Frontiers in Behavioral Neuroscience, 2010)
The chasing behavior of male blowflies after small targets belongs to the most rapid and virtuosic visually guided behaviors found in nature. Since in a structured environment any turn towards a target inevitably leads to a displacement of the entire retinal image in the opposite direction, it might evoke optomotor following responses counteracting the turn. To analyze potential interactions between the control systems underlying chasing behavior and optomotor following, respectively, we performed behavioral experiments on male blowflies and examined the characteristics of the two flight control systems in isolation and in combination. Three findings are particularly striking. (i) The characteristic saccadic flight and gaze style – a distinctive feature of blowfly cruising flights – is largely abandoned when the entire visual surroundings move around the fly; in this case flies tend to follow the moving pattern in a relatively continuous and smooth way. (ii) When male flies engage in following a small target, they also employ a smooth pursuit strategy. (iii) Although blowflies are reluctant to fly at high background velocities, the performance and dynamical characteristics of the chasing system are not much affected when the background moves in either the same or in the opposite direction as the target. Hence, the optomotor following response is largely suppressed by the chasing system and does not much impair chasing performance.